Clinical outcome of dental implant therapy in association with Le Fort I osteotomy preprosthetic surgery: A systematic review - Poli, Pier Paolo; de Nunes Lima, Valthierre [UNESP]; Souza, Francisley Ávila [UNESP]; Garcia, Idelmo Rangel [UNESP]; Maiorana, Carlo (Quintessence Publishing, 2019)
Purpose: The purpose of this systematic review was to evaluate the outcome of dental implant treatment in fully edentulous patients who underwent Le Fort I osteotomy as a preprosthetic surgical technique. Materials and Methods: A search was conducted of the PubMed (MEDLINE), EMBASE, Scopus, and Cochrane databases to identify records published from 1995 to 2017 dealing with Le Fort I osteotomy procedures for implant placement purposes. The primary outcomes of interest were the survival and success rates. The secondary outcomes consisted of the analysis of intrasurgical and postsurgical complications and the surgical and prosthetic loading protocols. Results: Overall, 20 articles were selected for data analysis. A total of 483 patients accounting for 3,596 implants were analyzed. The cumulative survival rate was 90.22% ± 0.8% at 10 years (mean: 59.20 ± 32.31 months). The cumulative success rate was 89.07% ± 1.3% at 10 years (mean: 62.82 ± 25 months). Higher survival rates were found for implants with a rough surface (P < .001) and for implants loaded with a delayed protocol (P < .001). The fracture of the palatine bone during the downfracture procedure was the main intrasurgical drawback, while sinus pathology and graft resorption were commonly observed during the postoperative healing. Surgical and prosthetic loading protocols were heterogenous. Conclusion: Based on this review, Le Fort I osteotomy might be considered a viable technique to recreate favorable conditions for implant-supported rehabilitations. Caution has to be taken when using machined implants, particularly in the case of a simultaneous approach.
Keywords: Bone augmentation; Dental implants; Le Fort I osteotomy